IMPLEMENTATION OF THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES ON THE RIGHT TO A FAIR TRIAL FOR PERSONS WITH INTELLECTUAL DISABILITIES - Praniko Imam Sagita; Hendri Abdul Qohar (JILPR Journal Indonesia Law and Policy Review, 2024)
Human rights are rights inherent in every individual as a gift from God Almighty, which must be respected, protected and fulfilled by the state. The Convention on the Rights of Persons with Disabilities (CRPD) is an international treaty that aims to promote, protect and guarantee the full and equal enjoyment of all human rights and fundamental freedoms by all persons with disabilities. This research aims to increase awareness and understanding of the rights of persons with intellectual disabilities, particularly in ensuring access to a fair trial in accordance with the principles of the Convention on the Rights of Persons with Disabilities (CRPD). This research uses a normative juridical method by analyzing international and national laws and regulations related to the implementation of the CRPD in ensuring the right to a fair trial for persons with intellectual disabilities. The results showed that although Indonesia has ratified the Convention on the Rights of Persons with Disabilities (CRPD), its implementation in the judiciary is still constrained by the lack of understanding of legal officials, limited facilities, bias against the right to testimony of persons with disabilities, and weak enforcement of regulations.